THE EFFECT OF FINANCIAL LITERATION ON INVESTMENT DECISION BEHAVIOR - Ni Putu Yeni Astiti; G. Oka Warmana; Mifthahul Hidayah (AIBPM Publisher, 2019)
Financial Literacy is a very broad concept. This study uses three dimensions of financial literacy, namely financial knowledge, financial behavioral and financial attitude. The purpose of this study was to determine the effect of financial knowledge, financial, and financial behavioral attitude towards investment decision on entrepreneurs in Bali. Collecting data with a questionnaire on investors who are members of the Komunitas Bisnis Tangan Di Atas (TDA) Bali, a total of 50 people as samples. The sampling method uses nonprobability sampling with an accidental sampling approach. The regression results show (1) financial knowledge does not affect investment decision making, (2) financial behavior does not affect investment decision making, (3) financial attitude has a positive effect on investment decision making